Pengaruh Tingkat Kesehatan, Pendidikan, Dan Pendapatan Terhadap Produktivitas Tenaga Kerja Di Kota Padang Panjang - Jefri Mahendra; Alimin; Himyar Pasrizal (DPPM Universitas Pelita Bangsa, 2025)
An abstract is often presented separate from the article, so it must be able to The purpose of this study is to analyze partially and simultaneously the influence of the human development index, health, education and income on labor productivity in Padang Panjang City. The type of research that the author uses is causative research using secondary data. The data in this study were collected by the author through the official website of the Padang Panjang City Central Statistics Agency and the official website of the West Sumatra Province Central Statistics Agency. Data processing using multiple linear regression analysis with data processing tools is SPSS. The results of the study show that partially the variables of health, education and income have a significant effect on labor productivity in Padang Panjang City. Simultaneously, the variables of health, education and income have a significant effect on labor productivity in Padang Panjang City with a very good level of influence of 82.2%, while the remaining 17.8% is explained by other variables outside this study.